2021
DOI: 10.1039/d0tb02499f
|View full text |Cite
|
Sign up to set email alerts
|

Double-acceptor conjugated polymers for NIR-II fluorescence imaging and NIR-II photothermal therapy applications

Abstract: Nanoparticles based double-acceptor conjugated polymers were developed by conventional methods. And subsequently NPs with bright NIR-II fluorescence signals and superior NIR-II PTT efficiency were successfully applied for NIR-II FI guided NIR-II PTT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 46 publications
1
73
0
Order By: Relevance
“…Semiconductor polymer dots (Pdots) are a new type of organic fluorescent material that has emerged in recent years. Compared with conventional fluorescent dyes, Pdots have broad absorption, symmetric narrow emission, high luminance, high photostability and large Stokes shift ( Chen et al, 2021 ). Therefore, nanoparticles composed of highly fluorescent semiconductor polymers are considered as an effective fluorescent probe and show promising applications in bioimaging, molecular detection, and guiding drug therapy.…”
Section: Categories Of Nir-ii Fluorescent Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…Semiconductor polymer dots (Pdots) are a new type of organic fluorescent material that has emerged in recent years. Compared with conventional fluorescent dyes, Pdots have broad absorption, symmetric narrow emission, high luminance, high photostability and large Stokes shift ( Chen et al, 2021 ). Therefore, nanoparticles composed of highly fluorescent semiconductor polymers are considered as an effective fluorescent probe and show promising applications in bioimaging, molecular detection, and guiding drug therapy.…”
Section: Categories Of Nir-ii Fluorescent Probesmentioning
confidence: 99%
“…Recent studies have shown that biological imaging in the second near-infrared region (NIR-II, 1,000–1700 nm) can achieve higher penetration depth (up to 20 mm) and spatial-temporal resolution, so as to obtain a better image quality ( Wang et al, 2014 ; Li and Pu, 2018 ). With the development of chemical synthesis, there have been several fluorescent probes employed for NIR-II biomedical imaging, including single-walled carbon nanotubes (SWCNTs), small organic molecules, rare-earth-doped nanoparticles (RENPs), quantum dots (QDs), conjugated polymers and other inorganic nanoparticles ( Antaris et al, 2016 ; Cai et al, 2019 ; Chen et al, 2020 ; Du et al, 2020 ; Mandal et al, 2020 ; Yu et al, 2020 ; Chen et al, 2021 ). In this paper, the recent developed fluorescent probes for NIR-II imaging and their biomedical applications are reviewed (shown in Figure 1 ) and prospected, in order to promote clinical translation and inspire new ideas for the development of NIR-II fluorescent imaging technology.…”
Section: Introductionmentioning
confidence: 99%
“…However, the applications of this technique is further limited due to its relatively shallow tissue penetration depth in the traditional NIR-I region ( Lyu et al, 2019 ). Currently, the biologically-related applications of NIR-II has aroused great interest, which can be used for NIR-II PTT and NIR-II fluorescence imaging ( Liu et al, 2019 ; Suo et al, 2019 ; Chen et al, 2021 ). It has the advantages of low light scattering, high spatial resolution and deep tissue penetration ( Yang et al, 2017a ).…”
Section: Introductionmentioning
confidence: 99%
“…Semiconducting polymer nanoparticles (SPNs) composed of completely organic compounds have been emerged as photothermal agents for tumor therapy [ 26 29 ]. Compared with other inorganic nanomaterials such as gold nanorods and carbon nanotubes, SPNs possess unique characteristics such as better biocompatibility, higher NIR absorption and photothermal conversion efficiency, feasibility and controllability [ 30 34 ].…”
Section: Introductionmentioning
confidence: 99%